Genus Pteraeolidia: Filogeni dan Faktor Geografi - Adelfia Papu; Farha Dapas; Parluhutan Siahaan (Universitas Sam Ratulangi, 2023)
Pteraeolidia is a member of Cladobranchia that can be found in Indonesia. This study aims to investigate the phylogenetic and geographyc relationship within Pteraeolidia species not only in Indonesia. Sequences of Pteraeolidia COXI gene, were extracted from the GenBank and were analysed using K3Pu+F+I+G4 model. Haplotypenetwork analyses was used for the specific investigation. The likelihood phylogenetic tree of Pteraeolidia reveals monophyletic of P. ianthina. However, it splits into two branches with high distance matrix. P. semperi joins into one branch, despite, five sequences of P. ianthina which joined in the brach cause the clade become nonmonophyly. P. semperi not only found in East Australia but also in Sulawesi and Pacific.